Quantitative-PCR Assessment of Cryptosporidium parvum Cell Culture Infection - Di Giovanni, George D. (American Society for Microbiology, 2005)
A quantitative TaqMan PCR method was developed for assessing the Cryptosporidium parvum infection of in vitro cultivated human ileocecal adenocarcinoma (HCT-8) cell cultures. This method, termed cell culture quantitative sequence detection (CC-QSD), has numerous applications, several of which are presented. CC-QSD was used to investigate parasite infection in cell culture over time, the effects of oocyst treatment on infectivity and infectivity assessment of different C. parvum isolates. CC-QSD revealed that cell culture infection at 24 and 48 h postinoculation was approximately 20 and 60%, respectively, of the endpoint 72-h postinoculation infection. Evaluation of three different lots of C. parvum Iowa isolate oocysts revealed that the mean infection of 0.1 N HCl-treated oocysts was only 36% of the infection obtained with oocysts treated with acidified Hanks' balanced salt solution containing 1% trypsin. CC-QSD comparison of the C. parvum Iowa and TAMU isolates revealed significantly higher levels of infection for the TAMU isolate, which agrees with and supports previous human, animal, and cell culture studies. CC-QSD has the potential to aid in the optimization of Cryptosporidium cell culture methods and facilitate quantitative evaluation of cell culture infectivity experiments.